The Prevalence and Motivation of the Undeclared Employment in Latvia - Nagle, Ieva; Ulmane, Ilvija; Sutova, Aleksandra; Bergmanis, Bruno; Juruss, Maris; Hudenko, Justina (Technium Social Sciences Journal, 2020)
Until recently a common practice to combat undeclared employment in Latvia was to provide wide inspections in risk economic sections. New knowledge about the motivation of undeclared employment motivation has raised considerable concerns about the quality of the existing practices. The goal of this study is to investigate the prevalence and motivation of the undeclared employment in Latvia in order to accept/confirm or to deny/reject these concerns. This paper delivers the results of qualitative analysis of the survey that authors undertook. The results show that the current definition of undeclared employment in Latvia cannot be considered as fully supported by society, because the perception of the need to declare employment differs significantly depending on the employment regularity and the relationship with the employer. The authors found that the results obtained in the study on the prevalence of undeclared income do not differ significantly from the results obtained in the previous study of Putnins and Sauka (2018) with the leading “hard math” motivation.